Suara Sang Dhomir : Eksporasi Vokal Spritualitas Pesantren Dalam Musik Kontemporer - Hayatussaadah, Sinta; Setiaji, Denden (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
Suara Sang Dhomir is a contemporary musical exploration that elevates the recitation of isim dhomir a grammatical element in Arabic commonly practiced in Islamic boarding schools (pesantren), as the primary source of sonic material. Traditionally viewed as a routine linguistic exercise, these recitations are transformed into a vocal composition lasting 5–7 minutes, without the use of musical instruments or conventional tonal systems. The creation process employs an experimental approach through techniques such as vocal layering, digital manipulation (including time-stretching and pitch-shifting), as well as the deliberate use of silence and pauses as both dramatic and spiritual elements. The composition is built on a layered human vocal structure, producing a listening experience that is reflective, contemplative, and emotionally resonant. This work offers a new discourse in tradition-based contemporary music, while also critiquing the academic formalism often found in religious musical interpretation. Through the concept of embodied sonic meditation, the piece demonstrates how the human voice at its most simple and spiritual can serve as a medium of aesthetic, inner, and cultural expression.